Out of the classroom, into the home: Medical and dental students' lessons learned from a Geriatrics home visit. Issue 9 (19th July 2022) - Goldlist, Kady; Beltran, Christine P.; Rhodes‐Kropf, Jennifer; Sullivan, Amy M.; Schwartz, Andrea Wershof
Abstract: Background: Home visits are an important part of Geriatrics education for medical and dental students (MS), and the lessons learned by students from these experiences inform further curriculum development. A mixed methods analysis of students' lessons learned from a single Geriatrics home visit shapes the future focus and impact of similar educational programs to ultimately improve the care of older adults. Methods: Over a 3‐year period at Harvard Medical School, approximately 495 first year MS participated in an educational Geriatrics home visit to learn about the geriatric assessment. Three hundred and forty‐eight students completed voluntary anonymous evaluation forms, rating whether their interest in geriatrics increased after the home visit and describing two lessons learned. We analyzed the student responses and conducted a qualitative content analysis of the lessons learned, identifying major themes within the Geriatrics 5Ms Framework (Mobility, Mind, Medications, Multicomplexity, and Matters Most). Results: Most students (70.7%) reported their interest in Geriatrics somewhat or greatly increased after the home visit. Three hundred and ten students (89% of participants) reported 605 lessons learned; 174 students' lesson learned related to Multicomplexity (56.1%), and 158 students reported a lesson related to Mobility (51%). Discussion: After a Geriatrics home visit, a majority of students report an increase interest in Geriatrics. The most common lessons learned relate to Mobility and Multicomplexity, essential areas of focus in a Geriatrics curriculum. Educational home visits are an important opportunity to increase student interest in geriatrics and build their skills to improve the care of older adults using the Geriatrics 5Ms Framework.